Multi-scale magnetic field structures in an expanding elongated plasma cloud with hot electrons subject to an external magnetic field - Garasev, Mikhail; Nechaev, Anton; Stepanov, Andrey; Kocharovsky, Vitaly; Kocharovsky, Vladimir (arXiv.org, 2022)
We carry out 3D and 2D PIC-simulations of the expansion of a magnetized plasma that initially uniformly fills a half-space and contains a semi-cylindrical region of heated electrons elongated along the surface of the plasma boundary. This geometry is related, for instance, to the ablation of a plane target by a femtosecond laser beam under quasi-cylindrical focusing. We find that the decay of the inhomogeneous plasma--vacuum discontinuity is strongly affected by an external magnetic field parallel to its boundary. We observe various transient phenomena, including the anisotropic scattering of electrons and the accompanying Weibel instability, and reveal various spatial structures of the arising magnetic field and current, including multiple flying apart filaments of a z-pinch type and slowly evolving current sheets with different orientations. The magnitude of the self-generated magnetic field can be of the order of or significantly exceed that of the external one. Such phenomena are expected in the laser and cosmic plasmas, including the explosive processes in the planetary magnetospheres and stellar coronal arches.